Profil gangguan fungsi kognitif pada pasien pasca stroke iskemik di RSUP Sanglah Denpasar Bali, Indonesia periode 2019 - Bimo Adi Laksono; Ketut Widyastuti; Sri Yenni Trisnawati (DiscoverSys Inc., 2019)
Background: Stroke is a disease that affects straightly to the brain. Stroke occured due to obstruction of blood vessel that contain blood-transportingÂ nutrients to the brain, which lead to impairment in brain function, as well as cognitive function. Because ofÂ unavailibility of data in Sanglah General Hospital, this research must be done. This study aims to determine the cognitive function profile of post ischemic stroke patient in Sanglah General Hospital based on 5 cognitive domains.Methods: This study is an observational study, collecting data by cross sectional. Data sources were obtained from primary data in the form of interview and MoCA-Ina Test with data retrieval methods using totally sampling technique. The accessible population was patients post ichemic stroke in Sanglah General Hospital that is in a good awareness and fit for MoCA-Ina test.Results: From 26 patients that are accessible, 21 patients were diagnosed with cognitive impairment, which the majority in 41-50 range of age with 9 patients, male with 14 patients, last education of Junior High School with 7 patients, and memory being a domain which is most impaired with mean of 55,38% score.Conclusion: The most affected domain is after an ischemic stroke is memory and visuospacial function